J.E. JASPER’S LITERARY WORK ON EDUCATING THE MASSES OVERSEAS: INDO-EUROPEAN LITERATURE FROM COLONIAL JAVA IN THE NETHERLANDS 1904-1910 - Rooyackers, Max (Sanata Dharma University, 2024)
This paper aims to analyze with the historical method how literature from the Dutch East Indies written by an Indo-European, a person from mixed Asian and European ancestors, attempted to educate the Dutch overseas in Europe. The early 20th century saw several technological developments which raised interest in Asia in the Netherlands and caused a spike in immigrants in the Indies. The Dutch were interested in reading about life in their colonial holdings overseas, especially those who were contemplating making a trip to the Indies. Many writings emerged to teach, warn, or push potential immigrants who wished to go to the Indies. However, those were mainly written by Dutch people who had lived or were living in the Indies temporarily. Indo-European writers had different concerns and interests from the Dutch, which pushed them to also write literary works that were partly aimed at the Dutch overseas. They hoped their writings would help them understand life in Java and to prepare properly. J.E. Jasper, an Indo-European colonial official, was the most outspoken critic of his literature. His work, heavily influenced by the Ethical Policy while developing his thoughts reminded and taught the Dutch about what was important about life in the Indies.